2001
DOI: 10.1038/sj.onc.1204430
|View full text |Cite
|
Sign up to set email alerts
|

FGF-8b increases angiogenic capacity and tumor growth of androgen-regulated S115 breast cancer cells

Abstract: Fibroblast growth factor 8 (FGF-8) is a secreted heparinbinding protein, which has transforming potential. Alternative splicing of the mouse Fgf-8 gene potentially codes for eight protein isoforms (a ± h) which di er in their transforming capacity in transfected cells. S115 mouse mammary tumor cells express a transformed phenotype and secrete FGF-8 in an androgen-dependent manner. In order to study the role of FGF-8 isoforms in the induction of transformed phenotype of breast cancer cells, we over-expressed FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 56 publications
2
49
0
Order By: Relevance
“…Tumours produced by FGF8b-expressing MCF7 cells were also shown to be more vascular than untransfected controls . Mattila et al (2001) have also demonstrated that FGF8b is able to stimulate migration and sprouting of mouse brain capillary endothelial cells. In this study, FGF8b promoted endothelial cell differentiation, organisation of capillary cells into cords and formation of lumen-like structures.…”
Section: Discussionmentioning
confidence: 87%
“…Tumours produced by FGF8b-expressing MCF7 cells were also shown to be more vascular than untransfected controls . Mattila et al (2001) have also demonstrated that FGF8b is able to stimulate migration and sprouting of mouse brain capillary endothelial cells. In this study, FGF8b promoted endothelial cell differentiation, organisation of capillary cells into cords and formation of lumen-like structures.…”
Section: Discussionmentioning
confidence: 87%
“…FGF2 [50] and FGF8b [17] can enhance endothelial cell reorganization on Matrigel. The process requires the activation of the proteolytic machinery, including type IV collagenase(s) and TIMPs production [51] as well as uPA and PAI-1 upregulation [52], a 6 b 1 integrin receptor engagement [53], PECAM-1 [54], and activation of the small GTPase Rac [55].…”
Section: Endothelial Cell Morphogenesismentioning
confidence: 99%
“…Recently, also the FGF8b isoform has been shown to stimulate endothelial cell proliferation in vitro [17]. FGFR engagement involves the activation of several parallel signaling pathways as a consequence of receptor autophosphorylation followed by recruitment of Shc, FRS2, and Crk adaptor molecules (for a review see [16]).…”
Section: Endothelial Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations